Pengaturan Hukum Pidana Adat dalam KUHP Baru dari Perspektif Asas Legalitas - Chandra, Yonatan Iskandar; Danil, Elwi; Zurnetti, Aria (Faculty of Law, Andalas University, 2023)
The discussion on Adat Criminal Law has returned to attention after promulgating the National Criminal Code. This is because the provisions regarding Adat Criminal Law are unknown and are not contained in the Criminal Code, which was previously in effect in Indonesia. The regulation of Adat Criminal Law in the form of positive law resulted in a change in the form of Adat Criminal Law itself, which was previously unwritten law to become written law. The change in form is also related to the Legality Principle, which is still maintained in the National Criminal Code. Based on this, it can be stated that the formulation of the problem in this study: (1) How is the concept of Adat criminal law regulation in the National Criminal Code? (2) What is the relationship between the nature of the Adat Criminal Law as unwritten law and its provisions in the National Criminal Code?; and (3) How is the regulation of Adat Criminal Law in the National Criminal Code according to the perspective of the Legality Principle? The method used in this research is normative legal research with statutory and conceptual approaches. The nature of the exploratory research uses primary, secondary, and tertiary legal sources. Based on the results of the study, it can be concluded that regulations regarding Adat Criminal Law in the National Criminal Code are as stipulated in Article 2 of the National Criminal Code, where Adat Crimes are laws that live in society in the form of unwritten law, and are still valid and developing in people's lives in Indonesia. However, the regulation of Adat Criminal Law in the National Criminal Code will cause problems when viewed from the perspective of the Legality Principle. The formulation that the Adat Criminal Law should be legalized through local law contradicts the essence of Adat Law itself and is the legality principle.